Realization of Super Large Autostereoscopic Display Wall - 田丰 杨雪 仇润鹤 刘锦高 (东华大学学报（英文版）, 2011)
The suitable lenticular lens for large panel autostereoscopic display was designed,and its optical transmission property was analyzed.The location of the best viewing zones and the relationship between screen size and the optimum viewing distance were proposed.On the basis of the original monitor,rear projection screen material suitable for large panel three-dimensional（3D） monitor and splicing method for 3D display wall were studied.Close to 150-inch-large panel stereo display wall was achieved.